2005
DOI: 10.1039/b505383h
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular rhodium-catalyzed [2 + 2 + 2] carbocyclization reactions of 1,6-enynes with symmetrical and unsymmetrical alkynes

Abstract: The crossed intermolecular rhodium-catalyzed [2 + 2 + 2] carbocyclization of carbon and heteroatom tethered 1,6-enynes can be accomplished with symmetrical and unsymmetrical alkynes, to afford the corresponding bicyclohexadienes in an efficient and highly selective manner.Transition metal-catalyzed carbocyclization reactions provide powerful and expeditious methods for the construction of complex polycyclic systems, which are generally not accessible via classical pericyclic reactions. 1 The metal-catalyzed [2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Rhodium catalyzed regioselective eyne-diyne[2 + 2 + 2]cycloadditions to give paracyclophanes [1304]. Rhodium-catalyzed intermolecular [2 + 2 + 2]cycloaddition of 1,6-enynes with alkynes to give bicyclic cyclohexadienes [1305]. Rhodium catalyzed [2 + 2 + 2]cycloadditions of 1,6-, 1,7-, and 1,8-diynes with isocyanates to give fused 2-pyridones [1306].…”
Section: Cycloadditionsmentioning
confidence: 99%
“…Rhodium catalyzed regioselective eyne-diyne[2 + 2 + 2]cycloadditions to give paracyclophanes [1304]. Rhodium-catalyzed intermolecular [2 + 2 + 2]cycloaddition of 1,6-enynes with alkynes to give bicyclic cyclohexadienes [1305]. Rhodium catalyzed [2 + 2 + 2]cycloadditions of 1,6-, 1,7-, and 1,8-diynes with isocyanates to give fused 2-pyridones [1306].…”
Section: Cycloadditionsmentioning
confidence: 99%
“…Gratifyingly, the non-coordinating solvent benzene (0.05 M) at 60 °C proved optimum, affording 21a in 95% yield (Entry 5). 35 Interestingly, the homodimerization adduct was not observed, whereas the product resulting from the competitive trapping of the metallacyclopentadiene D with a second equivalent of dimethyl acetylenedicarboxylate was produced in varying amounts, depending upon the concentration. Furthermore, the terminal acetylenic proton of the 1,6-enyne 7a proved to be crucial for catalytic activity, since the corresponding substituted derivatives, where R = Me, Ph or TMS, did not afford any of the carbocyclization adduct.…”
Section: Crossed Intermolecular Rhodium-catalyzed [2+2+2] Carbocyclizmentioning
confidence: 99%
“…Previous studies demonstrated that the overall efficiency could be improved dramatically by simply adjusting the nature of the solvent and/or counter-ion. 35 In light of this fact, we probed the effect of coordinating solvents, and silver salts with progressively weaker coordinating counter ions (Entries 2-5). Gratifyingly, the ethereal solvent tetrahydrofuran in combination with the tetrafluoroborate counter ion proved optimal in terms of efficiency (Entry 5), since these conditions completely suppressed the undesired homo-coupling of 1,6-enyne 7a.…”
Section: Regio-and Enantioselective Intermolecular Rhodium-catalyzed mentioning
confidence: 99%
“…[2] For this transformation, the complexes of cationic rhodium-(I) with biaryl diphosphine complexes are well established as highly active catalysts. Elegant examples of the asymmetric [2 + 2 + 2] cycloadditions of 1,6enynes and alkynes were pioneered by the groups of Evans [3] and Shibata (Figure 1). [4] By using activated alkenes instead of alkynes, the group of Tanaka has accomplished the produce of chiral substituted cyclohexenes.…”
mentioning
confidence: 99%